Dynamical systems: (VOL-4) Proceedings of the special program at Nankai Institute of Mathematics, Tianjin, China, September 1990-June 1991 - Shan-tao, Liao; Yen-chʻien, Yeh and Tong-Ren Ding (River Edge, London: World Scientific, 1993)
Covers such topics as the dynamics of an age structured epidemic model; harmonic solutions and subharmonic solutions for periodic Lotka-Volterra systems; classes of quadratic systems of differential equations in the plane; and bounded polynomial vector fields II